Properties of Central and Peripheral Concepts of Emotion in Japanese and Korean: An Examination Using a Multi-Dimensional Model - Park, Eun-Joo; Kikutani, Mariko; Suzuki, Naoto; Ikemoto, Machiko; Lee, Jang-Han (Frontiers in Psychology, 2022)
The concept of emotion can be organized within a hypothetical space comprising a limited number of dimensions representing essential properties of emotion. The present study examined cultural influences on such conceptual structure by comparing the performance of emotion word classification between Japanese and Korean individuals. Two types of emotional words were used; central concepts, highly typical examples of emotion, and less typical peripheral concepts. Participants classified 30 words into groups based on conceptual similarity. MDS analyses revealed a three-dimensional structure with valence, social engagement, and arousal dimensions for both cultures, with the valence dimension being the most salient one. The Japanese prioritized the social engagement over the arousal while the Koreans showed sensitivities to the arousal dimension. Although the conceptual structure was similar for the two countries, the weight of importance among the three dimensions seems to be different, reflecting each culture's values and communication styles.